2020
DOI: 10.1021/acsmedchemlett.9b00687
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Outlook for the Isosteric Replacement of Anilines

Abstract: Many promising drug candidates and pharmaceutical compounds fail due to idiosyncratic adverse drug reactions (IADRs), often arising from the formation of reactive metabolites. Among the "structural alerts" responsible, anilines are well-known to undergo deleterious metabolic processing, yet isosteric replacement strategies remain limited. Herein we discuss current art and potential new avenues of saturated isosteres to mitigate aniline-related toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…[3] Accordingly,b icyclo[1.1.1]pentylamine (BCPA) has been extensively targeted as ap rominent aniline bioisostere by creating unexplored druglike chemical space with varying levels of synthetic utility (Scheme 1A). [4] From as ynthetic point of view,propellane can be efficiently aminated by ringopening functionalization at the BCP bridgehead positions, where the internal central C À Cb ond of [1.1.1]propellane [5] can be readily cleaved under an anionic strain-release approach [6] and, more recently,aradical pathway affording the requisite substituted BCPAc ompounds (Scheme 1B). [7] Baran et al disclosed the strain-release amination of propellane by employing deprotonated dialkyl amines to access monosubstituted BCPAs.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Accordingly,b icyclo[1.1.1]pentylamine (BCPA) has been extensively targeted as ap rominent aniline bioisostere by creating unexplored druglike chemical space with varying levels of synthetic utility (Scheme 1A). [4] From as ynthetic point of view,propellane can be efficiently aminated by ringopening functionalization at the BCP bridgehead positions, where the internal central C À Cb ond of [1.1.1]propellane [5] can be readily cleaved under an anionic strain-release approach [6] and, more recently,aradical pathway affording the requisite substituted BCPAc ompounds (Scheme 1B). [7] Baran et al disclosed the strain-release amination of propellane by employing deprotonated dialkyl amines to access monosubstituted BCPAs.…”
Section: Introductionmentioning
confidence: 99%
“…Already recognised by Eaton in the 1990s as a potential '3D phenyl bioisostere', 3 it is through the later proposed concept 'Escape from Flatland', 9 that pharmaceutical research focused on the replacement of benzene rings with 3D saturated isosteres to modulate pharmacokinetics properties (ADME), 10,11 resulting in an increasing demand for access to cubane building blocks. [12][13][14] The isosteric relationship is based on the cubane diagonal (2.72 Å) being close to that of benzene (2.79 Å) ( Figure 1c). Key examples of the study of cubane analogues of drug and agrochemical molecules include diflucuburon, the cubane analogue of diflubenzuron used as insecticidal ( Figure 1c) by Tsanaktsidis, Savage, Williams et al, and imatinib, by Nicolaou, Vourloumis, Stepan et al, which showed the highest inhibitory activity against the desired target and the greatest cytotoxicity values against cancer cell lines, compared to other saturated cycloalkyl derivatives (Figure 1c).…”
mentioning
confidence: 99%
“…Furthermore, GRL-0617 contains a toxic chemical moiety, an aniline group. Nearly one-third of drugs that have been withdrawn from the market, or that have black-box warnings associated with idiosyncratic adverse drug reactions (IADRs), contain an aniline group [ 44 , 45 , 46 , 47 ]. GRL-0617 has not yet been tested in clinical trials, or in animal studies, to establish safety or side-effects.…”
Section: Introductionmentioning
confidence: 99%